A new species of Multidentorhodacarus (Mesostigmata: Rhodacaridae) from Brazil, complementary description of Multidentorhodacarus squamosus Karg and a key to the world species of the genus - Azevedo, Emiliano B. De [UNESP]; Sarmento, Renato A.; Castilho, Raphael C. [UNESP] (Systematic and Applied Acarology Society, 2019)
Multidentorhodacarus tocantinensis sp. nov. is described based on the morphology of adult females collected from litter and soil in the Cerrado biome of the State of Tocantins, north of Brazil. The holotype and paratypes of M. squamosus Karg, 2000 were examined, given that this species was also found in this study, and complementary morphological information about it is provided. A key for the separation of females of the 20 recognizable world species of Multidentorhodacarus Karg is provided.
Keywords: Rhodacaroidea; soil mites; taxonomy